2021
DOI: 10.1039/d0na00936a
|View full text |Cite
|
Sign up to set email alerts
|

The improved photocatalytic activity of highly expanded MoS2 under visible light emitting diodes

Abstract: Improved photocatalytic activity of highly expanded MoS2 under visible light emitting diode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 67 publications
2
18
1
Order By: Relevance
“…These observations confirm the formation of MSO composites. 19,34 It is worthy to note that generally in the MoS 2included QDs, nanoflakes/sheets, and even bulks, the Mo 4+related signals are located at around 229 and 232−233 eV. 35,36 These are a little bit different from the results presented here which can be assigned to the distinct NW morphology in the present MoS 2 @MoO 3 composites.…”
Section: Synthesis Of Qdscontrasting
confidence: 90%
See 1 more Smart Citation
“…These observations confirm the formation of MSO composites. 19,34 It is worthy to note that generally in the MoS 2included QDs, nanoflakes/sheets, and even bulks, the Mo 4+related signals are located at around 229 and 232−233 eV. 35,36 These are a little bit different from the results presented here which can be assigned to the distinct NW morphology in the present MoS 2 @MoO 3 composites.…”
Section: Synthesis Of Qdscontrasting
confidence: 90%
“…The key parameters determining the optical properties of such transition-metal trioxides or dichalcogenides are their shape and size. For example, the absorption edge for pure MoS 2 nanosheets is located at a wavelength range of 500−610 nm, 8,34 while hierarchical microspheres of PEGylated MoS 2 nanosheets and MoO 3 nanorods show absorption at short wavelengths. 30 Besides, the UV−vis absorption edge reported for blue-emissive MoS 2 QDs is also located at shorter wavelengths below 350 nm.…”
Section: Synthesis Of Qdsmentioning
confidence: 99%
“…62 Numerous researches in the past have shown that MoS 2 is an efficient photocatalytic material for water splitting, degrading pollutants and photosynthesis. [67][68][69][70] However, pristine MoS 2 , faces the problem of high recombination rate (among many other problems) owing to stagnancy of the photogenerated charge carriers in the same spatial regions. 62,67 This problem of charge stagnancy and thus efficient separation and thereby collection has been achieved via forming a HS with ZnO.…”
Section: Introduction To Heterostructures and Its Significancementioning
confidence: 99%
“…19 In particular, 2D MoS 2 exhibits a tunable bandgap (1.2 eV to 1.8 eV, visible to near-infrared), high chemical reactivity, low toxicity, more catalytically active sites, a large surfaceto-volume ratio, and high charge-carrier mobility with broad absorption in the visible light range, which makes it an excellent catalyst for visible-light-driven redox reactions. [20][21][22][23][24] The crystalline MoS 2 consists of basal and edge planes, where the former is inherently and thermodynamically favored to have higher surface exposure. 25 Despite this, the photocatalytic activity of MoS 2 is often limited as a result of its dependency on the availability of edge sites.…”
mentioning
confidence: 99%
“…37 Also, Lai et al showed interlayer expanded MoS 2 where the layer-expanded MoS 2 exhibited high photocatalytic activity. 22 However, the chemical functionalization of MoS 2 nanosheets are still limited and can be accomplished by various means of modifying non-covalent or covalent bonding interactions with metals and non-metals as well as with other organic molecules. 38 Specifically, it is always worthwhile to functionalize 2D-MoS 2 for enhancing catalytic activity while creating an expanded interlayer-structure and an increased bandgap for improving its functionalities from catalysis to photocatalysis.…”
mentioning
confidence: 99%